2011
DOI: 10.1002/jrs.3073
|View full text |Cite
|
Sign up to set email alerts
|

Microwave monitoring of silver nanoparticle sintering for surface‐enhanced Raman scattering substrates

Abstract: One of the most widely used methods for surface‐enhanced Raman scattering (SERS) employs silver or gold nanoparticles either in colloidal suspension or in the dry‐drop form. In such substrates the SERS amplification factors depend critically on the interparticle distances. Here, we report that microwave absorption as a function of temperature in dry‐drop substrates can be used as a probe to demarcate temperature regions for thermal annealing to produce SERS substrates with very high amplification factors. Copy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…However, when the sintering of AgNCs occurs, the G band intensity is expected to be suppressed because of the absence of the hot spots of AgNCs. 63 As seen in the temperature dependence of the AgNC height ( Fig. 5 ), a slight decrease in AgNC height was confirmed at 222 °C.…”
Section: Resultssupporting
confidence: 54%
“…However, when the sintering of AgNCs occurs, the G band intensity is expected to be suppressed because of the absence of the hot spots of AgNCs. 63 As seen in the temperature dependence of the AgNC height ( Fig. 5 ), a slight decrease in AgNC height was confirmed at 222 °C.…”
Section: Resultssupporting
confidence: 54%
“…Figueroa et al . reported that microwave absorption as a function of temperature in dry‐drop substrates can be used as a probe to demarcate temperature regions for thermal annealing to produce SERS substrates with very high amplification factors . Fu and co‐workers investigated plasmonic enhancement arising from bimetallic (Au/Ag) hierarchical structure and addressed the fundamental issues relating to the design of multilayered nanostructures for SERS.…”
Section: Sersmentioning
confidence: 99%
“…Stimulated Raman scattering (SRS) microscopy is a powerful optical imaging technique that uses the intrinsic vibrational contrast of molecules to provide chemical maps of biological cells and tissues. Due to its label-free imaging capability and subcellular spatial resolution, SRS imaging has shown great promise in many biological and biomedical applications such as metabolic studies, drug imaging, tissue diagnosis [1][2][3][4][5][6][7][8]. Recent work has shown that twocolor SRS imaging can generate virtual H&E images that are useful for intraoperative cancer detection and margin analysis [9,10].…”
Section: Introductionmentioning
confidence: 99%